THE USE OF SELF-MONITORING URINE CHART (PURI) IN OLDER ADULTS TO PREVENT DEHYDRATION: A LITERATURE REVIEW - Sumeru, Annas; Mustikasari, Dian (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Introduction: adequate daily water intake help reduce dehydration. The most vulnerable age group from dehydration are newborn and older adults. One and most easy to use by the older adults in detecting hydration status is using urine colour chart. The colour of the urine in the chart describes the different condition of body fluid.Objective: This study purposes to review some works of literature on the use of Self Urine Assessment (PURI) on older adults to Prevent Dehydration.Method: Journal article search was using multiple electronic databases as Pubmed, Google Scholar, and Science Direct from 2015 to 2019. Keyword used were ?self-monitoring hydration?, ?urine colour assessment?, and ?older adults? to obtain four articles for review.Results: The previous study shows that the usual clinical hydration diagnostic measurement can?t be used to detect dehydration accurately.Discussion: Self-monitoring hydration by using the urine chart still be the fastest, cheap yet fast to help older adults monitoring hydration status.